Disseminated Histoplasmosis Infection in HIV-Negative Patients: Series Case and Literature Review - Ferrisse, Túlio Morandin [UNESP] (2021)
Histoplasmosis is a deep mycosis distributed worldwide and caused by Histoplasma capsulatum. Development countries and underdeveloped countries already considered an endemic disease, and its etiology comes from fungi located in soil contaminated with bird and bat droppings. Habits such as tobacco and alcohol consumption can be factors that can help to the development of disseminated histoplasmosis mainly in immunocompetent patients. Clinical manifestations can include fever, weakness, weight loss, hepatosplenomegaly, mucocutaneous lesions, and ulcer oral lesions. Oral lesions represents a commonly manifestation in the disseminated form of the disease, and it is more frequently observed in immunocompromised patients, mainly on HIV-positive patients. In this study, we presented five cases of disseminated histoplasmosis on HIVnegative patients diagnosed with lesions located in oral cavity and we performed a literature review about cases of disseminated histoplasmosis lesions in head and neck region on HIV-negative patients associating possible factors that may contribute to lesions formatting.